Cardiovascular oxygen transport and peripheral oxygen extraction capacity contribute to acute heat tolerance in European seabass - Anttila Katja; Mauduit Florian; Kanerva Mirella; Götting Miriam; Nikinmaa Mikko; Claireaux Guy (Elsevier Inc., 2023)
This study evaluated whether different parameters describing cardiovascular function, energy metabolism, oxygen transport and oxidative stress were related to the critical thermal maximum (CTMAX) of European seabass (Dicentrarchus labrax) and if there were differential changes in these parameters during and after heat shock in animals with different CTMAX in order to characterize which physiological features make seabass vulnerable to heat waves. Seabass (n = 621) were tested for CTMAX and the physiological parameters were measured in individuals with good or poor temperature tolerance before and after a heat shock (change in temperature from 15 °C to 28 °C in 1.5 h). Fish with good thermal tolerance had larger ventricles with higher maximal heart rate during the heat shock than individuals with poor tolerance. Furthermore, they initially had a high ventricular Ca2+-ATPase activity, which was reduced to a similar level as in fish with poor tolerance following heat shock. The activity of heart lactate dehydrogenase increased in fish with high tolerance, when they were exposed to heat shock, while the aerobic enzyme activity did not differ between groups. The tolerant individuals had smaller red muscle fibers with higher myoglobin content than the poorly tolerant ones. The poorly tolerant individuals had higher hematocrit, which increased with heat shock in both groups. The poorly tolerant individuals had also higher activity of enzymes related to oxidative stress especially after heat shock. In general, CTMAX was not depending on merely one physiological factor but several organ and cellular parameters were related to the CTMAX of seabass and when working in combination they might protect the highly tolerant seabass from future heat waves.